2022
DOI: 10.3389/fneur.2022.1021877
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of neutrophil-to-lymphocyte ratio in patients with traumatic brain injury: A systematic review

Abstract: Traumatic brain injury (TBI) places a heavy load on healthcare systems worldwide. Despite significant advancements in care, the TBI-related mortality is 30–50% and in most cases involves adolescents or young adults. Previous literature has suggested that neutrophil-to-lymphocyte ratio (NLR) may serve as a sensitive biomarker in predicting clinical outcomes following TBI. With conclusive evidence in this regard lacking, this study aimed to systematically review all original studies reporting the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…These differing temporal responses and functions indicate that a higher NLR (higher neutrophils and lower lymphocytes) may predict worse outcomes in TBI patients. Currently, studies regarding NLR in TBI have demonstrated that higher NLR is an independent prognostic factor for mortality in severe TBI [ 17 , 20 , 21 ]. However, due to the relatively new implementation of this test, there remains no large-scale statistical analysis for the use of NLR in TBI for bleeding, neurosurgical management, and outcome determination.…”
Section: Introductionmentioning
confidence: 99%
“…These differing temporal responses and functions indicate that a higher NLR (higher neutrophils and lower lymphocytes) may predict worse outcomes in TBI patients. Currently, studies regarding NLR in TBI have demonstrated that higher NLR is an independent prognostic factor for mortality in severe TBI [ 17 , 20 , 21 ]. However, due to the relatively new implementation of this test, there remains no large-scale statistical analysis for the use of NLR in TBI for bleeding, neurosurgical management, and outcome determination.…”
Section: Introductionmentioning
confidence: 99%